Octopaminergic modulation of temporal frequency tuning of a fly visual motion-sensitive neuron depends on adaptation level - Lüders, Janina; Kurtz, Rafael (Frontiers in Integrative Neuroscience, 2015)
Several recent studies in invertebrates as well as vertebrates have demonstrated that neuronal response characteristics of sensory neurons can be profoundly affected by an animal's locomotor activity. The functional consequences of such state-dependent modulation have been a matter of intense debate. In flies, a particularly interesting finding was that tethered walking or flying causes not only general response enhancement of visual motion-sensitive neurons, but also broadens their temporal frequency tuning towards higher values. However, in other studies such state-dependent alterations of neuronal tuning functions were not found. We hypothesize that these discrepancies were due to different adaptation levels of the motion-sensitive neurons, resulting from the use of different stimulation protocols. This is plausible, because the strength of adaptation during ongoing stimulation was shown to be affected by chlordimeform (CDM), an agonist of the insect neuromodulator octopamine, which mediates state-dependent modulation. Our results show, that CDM causes broadening of the temporal frequency tuning of the blowfly's visual motion-sensitive H1 neuron only in the adapted state, but not prior to the presentation of adapting motion. Thus, our study indicates that seemingly conflicting results on the locomotor state-dependence of neuronal tuning functions are consistent when considering the neurons' adaptation level. Moreover, it demonstrates that stimulation history has to be considered when the significance of state-dependent modulation of sensory processing is interpreted.